2022
DOI: 10.3390/life12020233
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cortical Bone Thickness Variations in the Tibial Diaphysis of Running Rats

Abstract: A cell-mechanobiological model is used for the prediction of bone density variation in rat tibiae under medium and high mechanical loads. The proposed theoretical-numerical model has only four parameters that need to be identified experimentally. It was used on three groups of male Wistar rats under sedentary, moderate intermittent and continuous running scenarios over an eight week period. The theoretical numerical model was able to predict an increase in bone density under intermittent running (medium intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Running exercise is recognized as an effective way to improve bone mechanical properties, and running with the appropriate intensity could increase bone density and strength [ 4 , 5 ]. Several experiments considered that the fracture load, cortical bone thickness, and tissue-level elastic modulus in the rat femoral and tibial cortical bone structures significantly increased under treadmill running at low or moderate intensity [ 6 8 ]. However, different viewpoints exist in the studies on the effects of high-intensity running on the mechanical properties of cortical bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running exercise is recognized as an effective way to improve bone mechanical properties, and running with the appropriate intensity could increase bone density and strength [ 4 , 5 ]. Several experiments considered that the fracture load, cortical bone thickness, and tissue-level elastic modulus in the rat femoral and tibial cortical bone structures significantly increased under treadmill running at low or moderate intensity [ 6 8 ]. However, different viewpoints exist in the studies on the effects of high-intensity running on the mechanical properties of cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…Current experiments can obtain the macro- and nano-levels mechanical parameters but have difficulties in measuring the micro-level mechanical parameters in cortical bone structure [ 15 , 16 ]. Most studies only reported the changes in the microstructural morphology parameters under different loading environments [ 6 , 12 ]. The effects of micromechanical parameters on cortical bone fracture performance are significant, especially for micro-level failure strain in the osteon [ 17 ].…”
Section: Introductionmentioning
confidence: 99%